Avaliação do bloqueio neuromuscular residual e do bloqueio neuromuscular tardio na sala de recuperação pós-anestésica em pacientes submetidos à colecistectomia videolaparoscópica - Pedro Marcos Silva e Gonçalves (2020)
Background and Objectives: The use of neuromuscular blockers in surgical practice represented a milestone for anesthesiology. The use of these drugs may cause residual neuromuscular blockade and objective monitoring is essential to ensure recovery of muscle strength. The objective of this study was to estimate the incidence of residual neuromuscular block and late neuromuscular block in the post anesthesia care unit (PACU). Methods: Eighty-five patients who underwent general anesthesia participated in the study. Forty-three patients were included in the Cisatracurium Group and forty-two patients in the Rocuronium Group. The intensity of neuromuscular block was assessed by the sequence of four stimuli (SFS) / “train of four” (TOF). Reversal of neuromuscular block was performed with neostigmine and atropine administration. The patient with residual neuromuscular block was considered when the TOF value was of less than 90% in the post anesthesia care unit (PACU). Results: In the Cisatracurium Group, 39.53% of the patients presented TOF below 90% in the post anesthesia care unit (PACU). In the Rocuronium Group, 40.48% of the patients presented TOF below 90%. Regarding late neuromuscular block at PACU, 32.56% of patients in the Cisatracurium Group had such alteration and, in the Rocuronium Group, 16.67% of patients. The short duration of surgery and advanced ages were related to the higher occurrence of adverse events such as the need for ventilatory assistance and supplemental oxygen delivery in the nasal catheter (p < 0.05). Conclusions: It was found that the incidence of residual neuromuscular blockade remains significant despite the use of intermediate action blockers and reversers. Objective monitoring of neuromuscular block is effective for the diagnosis of residual neuromuscular block. Further studies with specific reversers are still needed to evaluate the role of these drugs in preventing residual neuromuscular block.